A problem by Anish Roy

Level 2

For any positive integer n n , let n \langle{n}\rangle denote the closest integer to n \sqrt{n} . Evaluate n = 1 2 n + 2 n 2 n \displaystyle \sum_{n=1}^{\infty} \frac{2^{\langle{n}\rangle}+2^{-\langle{n}\rangle}}{2^{n}}


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Anish Roy
Aug 29, 2017

Squaring ( m 1 2 ) (m-\frac{1}{2}) we get m 2 m + 1 4 m^{2}-m+\frac{1}{4} . So n m + 1 2 \sqrt{n}\geq m+\frac{1}{2} when n m 2 m + 1 4 n \geq m^{2}-m+\frac{1}{4} , but n n is an integer, so n m 2 m + 1 n \geq m^{2}-m+1 . Squaring ( m + 1 2 ) (m+\frac{1}{2}) we get m 2 + m + 1 4 m^{2}+m+\frac{1}{4} so n < m + 1 2 \sqrt{n}< m+\frac{1}{2} when n < m 2 + m + 1 4 n<m^{2}+m+\frac{1}{4} , but n n is an integer, so n m 2 + m n \leq m^{2}+m . Therefore, n = m \langle{n}\rangle=m , provided n [ m 2 m + 1 , m 2 + m ] n \in [m^{2}-m+1,m^{2}+m] . We can now rewrite our sum as: n = 1 2 n + 2 n 2 n = m = 1 k = m 2 m + 1 m 2 + m 2 m + 2 m 2 k = m = 1 2 2 m + 1 2 m k = m 2 m + 1 m 2 + m 1 2 k = m = 1 2 2 m + 1 2 m + m 2 m + 1 k = 0 2 m 1 1 2 k = m = 1 2 2 m + 1 2 m 2 + 1 × 1 2 2 m 1 2 1 = m = 1 2 2 m + 1 2 m 2 + 1 × 2 2 m 1 2 2 m 1 = m = 1 2 4 m 1 2 m 2 + 2 m = m = 1 ( 2 1 ( m 1 ) 2 2 1 ( m 1 ) 2 ) = 2 1 + 2 0 = 3 \begin{aligned} \displaystyle \sum_{n=1}^{\infty} \frac {2^{\langle{n}\rangle}+2^{-\langle{n}\rangle}}{2^{n}} &= \displaystyle \sum_{m=1}^{\infty} \sum_{k=m^2-m+1}^{m^2+m} \frac {2^m+2^{-m}}{2^k} \\ & = \displaystyle \sum_{m=1}^{\infty} \frac {2^{2m}+1}{2^m} \sum_{k=m^2-m+1}^{m^2+m} \frac {1}{2k} \\ & = \displaystyle \sum_{m=1}^{\infty} \frac {2^{2m}+1}{2^{m+m^2-m+1}} \sum_{k=0}^{2m-1} \frac {1}{2k} \\ &= \displaystyle \sum_{m=1}^{\infty} \frac {2^{2m}+1}{2^{m^2+1}} \times \frac {1-2^{-2m}}{1-2^{-1}} \\ & = \displaystyle \sum_{m=1}^{\infty} \frac {2^{2m}+1}{2^{m^2+1}} \times \frac {2^{2m}-1}{2^{2m}-1} \\ & = \displaystyle \sum_{m=1}^{\infty} \frac {2^{4m}-1}{2^{m^2+2m}} \\ & = \displaystyle \sum_{m=1}^{\infty}(2^{1-(m-1)^2}-2^{1-(m-1)^2}) \\ & =2^1+2^0=3 \end{aligned} The last step follows from the fact that even and odd sub-sums telescope. So, just the first even and odd terms survive. So our answer is 3 \boxed{3}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...